Home Immunization with Palivizumab-A Randomized Pilot Study Describing Safety Aspects and Parents' Preferences - Christina Ebersjö; Eva Berggren Broström; Inger Kull; Anna Lindholm Olinder (MDPI AG, 2023)
Among prematurely born infants and newborns with chronic conditions, a respiratory syncytial virus (RSV) infection may cause (re-)admission and later respiratory complications. Therapeutic protection is possible with monthly injections of a specific monoclonal antibody, palivizumab, during RSV season. Standard care is giving up to five injections in clinic-based settings. Immunization at home could be an alternative to standard care for vulnerable infants to reduce the number of revisits and associated risk of RSV infection. The aim of this randomized pilot trial was to evaluate safety aspects and explore parents' preferences of home versus hospital immunization with palivizumab during one RSV season. Immediate adverse events (AEs) were observed and registered by a pediatric specialist nurse. Late-onset AEs were reported by parents. Parents' perceptions were collected through a questionnaire and analyzed using content analysis. The study population consisted of 43 infants in 38 families. No immediate AEs occurred. Three late-onset AEs were reported in two infants in the intervention group. Three categories emerged in the content analysis: (1) protect and watch over the infant, (2) optimal health and well-being for the whole family, and (3) avoid suffering for the infant. The study results show that home immunization with palivizumab is feasible if safety aspects are considered and that parental involvement in the choice of place for immunization after a neonatal intensive care experience can be important.